Pendampingan Posyandu Mawar Putih 5 di Dusun Pabelan 4 melalui Pengelolaan Media Sosial dalam Upaya Pencegahan Stunting - Nurul Hidayah; Ihsan Taufiqurohman; Azis Maulana; Muhammad Isa Aliyudin; Aji Setyawan (Jurnal Surya Masyarakat, 2025)
Stunting is a disorder of growth and development in children due to long-term malnutrition. In Pabelan Hamlet 4 there are 9 children and 1 is suffering from malnutrition which results in stunted growth and development. One of the initiatives implemented in Pabelan 4 Hamlet is the monthly Supplementary Food Provision (SFP) program. However, this step has not been effective. Therefore, a more holistic approach is needed to address this problem comprehensively. This condition is the background for the KKN PPMT X team to provide assistance to the Mawar Putih 5 integrated health service post in Pabelan 4 Hamlet through social media management in an effort to prevent stunting. The implementation method of KKN PPMT X uses a socialization approach on social media management, training in creating accounts, videos, and posters using artificial intelligence technology, as well as assistance and evaluation in the form of checking and monitoring social media accounts. The results of the mentoring and evaluation showed that the schedule and management for uploading video content and posters uploaded on social media had begun to be structured, and there was an increase in the number of visits to the Mawar Putih 5 integrated health post from 60% to 100%. KKN PPMT X proved that with an approach through social media, Mawar Putih 5 integrated health service post was able to reduce stunting rates in Pabelan 4 Hamlet by providing interesting content for education in the wider community.